Identification and functional analysis of Tex11 and Meig1 in spermatogenesis of Hyriopsis cumingii - Huo, Yingduo; Gu, Yang; Cao, Mulian; Mao, Yingrui; Wang, Yayu; Wang, Xiaoqiang; Wang, Guiling; Li, Jiale (Frontiers in Physiology, 2022)
The process of spermatogenesis is complex and controlled by many genes. In mammals, Testis-expressed gene 11 (Tex11) and meiosis expressed gene 1 (Meig1) are typical spermatogenesis-related genes. In this study, we obtained the full length cDNAs for Tex11 (3143bp) and Meig1 (1649bp) in Hyriopsis cumingii by cloning. Among them, Hc-Tex11 contains 930 amino acids and Hc-Meig1 contains 91 amino acids. The protein molecular masses (MW) of Hc-Tex11 and Hc-Meig1 were 105.63 kDa and 10.95 kDa, respectively. Protein secondary structure analysis showed that Hc-TEX11 protein has three TPR domains. The expression of Hc-Tex11 and Hc-Meig1 in different tissues showed higher levels in testes. At different ages, the expression of Hc-Tex11 and Hc-Meig1 was higher levels in 3-year-old male mussels. During spermatogenesis, the mRNA levels of Hc-Tex11, Hc-Meig1 gradually increased with the development of spermatogonia and reached a peak during sperm maturation. Hc-Tex11 and Hc-Meig1 mRNA signals were detected on spermatogonia and spermatocytes by in situ hybridization. In addition, RNA interference (RNAi) experiments of Hc-Tex11 caused a down-regulated of Dmrt1, KinaseX, Tra-2 and Klhl10 genes and an up-regulated of β-catenin gene. Based on the above experimental results, it can be speculated that Hc-Tex11 and Hc-Meig1 are important in the development of the male gonadal and spermatogenesis in H. cumingii, which can provide important clues to better comprehend the molecular mechanism of Tex11 and Meig1 in regulating spermatogenesis of bivalves.